STUDENTS’ COLLAGE STRATEGIES TO OVERCOME THE ANXIETY IN DRAMA PERFORMANCE - Rahmalia, Indah (TELL - US JOURNAL, 2019)
Anxiety is always accured when students have drama performance because they have to speak English well in front of many people. Drama performance becomes the challenge for students since they are not only speak but also have a good performance on stage. To have a good performance, students should overcome their anxiety. This research is aimed to know what the students’ strategies in overcoming the anxiety in drama performance. The participants of this research were English department students of STKIP Abdi Pendidikan Payakumbuh who selected by using purposive sampling.The source of the data was questionnaire through some indicators from (O’Hair, 2010). They are boost confident, learn from feedback, activate the relaxation response, and use movement. It is consists of 30 items to 49 students which was analyzed by following some steps suggested by (Gay, Mills, and Airasian, 2011), they are data managing, reading and memoing, description, classifying, interpreting, writing report. The result showed that  boost confident strateg was 1850 points (33,17%) in highest score and movement strategy was 933 points (16,74%) as the lowest score Keywords: anxiety, drama performance, strategies to overcome anxiety